Rethinking the "dual causality principle" in Old Testament research - a philosophical perspective - Gericke, Jaco (Old Testament essays, 2015)
Reframing an old idea in philosophical theology, OT scholars have for the last half-century spoken of what has come to be known as the "dual causality principle"(DCP). The latter is supposed to denote a folk-metaphysical assumption in some OT texts characterized by the assignment of both divine and human causes to account for certain states of affairs. In this article the author challenges the consensus and argues that since the notion of causes is also a philosophical matter the theory behind the DCP may be supplemented by a descriptive metaphysical perspective. Typologies of causation show that the DCP is too simplistic and vague a concept since it ignores a host of complex metaphysical distinctions about causal types, relations and theories. Ultimately, causation in the OT is a complex phenomenon and technically not reducible to duality, causality, or to a principle of any sort.